When “Wait and See” may be the Best Option: Two Case Reports of Left Main Artery Spontaneous Dissection - Castelo, Alexandra; da Silva, Tiago P.; Ramos, Ruben; Mano, Tânia Branco; Ferreira, Rui Cruz (Current Cardiology Reviews, 2022)
Introduction: Spontaneous coronary artery dissection (SCAD) is frequently underdiagnosed, and the most appropriate management is unknown, particularly in high-risk anatomical subsets. Case Reports: Two cases of females in their 60-70s with few cardiovascular risk factors or relevant past medical history, who presented acute myocardial infarction, have been presented. Both were submitted to invasive coronary angiography, with a suspicion of SCAD in both cases, which was later supported by coronary computed tomography angiography (CCTA). They were managed conservatively under close monitoring, with a favorable outcome. Repeated CCTA showed significant improvement, and both patients remained asymptomatic and free from complications 6 and 12 months after the initial event. Conclusion: The recognition of spontaneous coronary artery dissection is essential for the correct management of these cases because, unlike acute coronary syndrome due to atherosclerotic disease, the results of revascularization in those patients are suboptimal and conservative management is probably the best option, even in patients with high-risk anatomy.
Keywords: asymptomatic